Heterocyclic Azo Dyes Derived from Adenine: Synthesis, Spectral Characterization, a wool Dying - Abd, Zaid Zuhair; Abbas, Alyaa khider (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The novel (La-PAA) of the ligand 8-[3-(pyrazoyl)azo]Adenine (PAA) was synthesized with the molar ratio (1:3), which was appointed by using the mole ratio method. The C.H.N.S elemental analysis, magnetic measurement, thermal analysis, and spectral methods (UV-Vis, FTIR, and HNMR) were employed to support the mode of binding and geometrical structure for ligand (PAA) and (La-PAA) complex. The FTIR and 1H N.M.R. spectral results showed that the (PAA) acts as neutral N, N-bidentate with La (III), as well as the absorption results in specific octahedral structures for (La-PAA) complex. The thermal decomposition of the (PAA) ligand and its (La-PAA) complex performed many steps, and the (La-PAA) complex is more thermal stable than the free ligand. The dyeing performance of the free ligand and (La-PAA) complex was tested, and they have straightforward and bright colors. The photostability of the free ligand (PAA) and [La(PAA)3]Cl3.3H2O complex in ethanol at a concentration of (10-4M) and subjecting them to ultraviolet (U.V.) radiation for two hours at room temperature. Finally, this research aimed to synthesize and characterize the ligand (PAA) and its complex, as well as test the ability of the ligand (PAA) and its complex on wool fiber.